?EXTRACTION, SEPARATION AND DETERMINATION OF COPPER (II) AND IRON (III), BY HIGH MOLECULAR WEIGHT AMINES - MASOOD, HAJRA; KHAN, KAMIN; KHAN, TAJ ALI (Biological Sciences - PJSIR, 1995)
The work describes the development of analytical methods for the extraction, separation and trace determination of Cu (II) in the presence of macro-amount of Fe (III) and the application of these methods to the anlayses of geologi- cal samples i.e. the ores of Cu such as malachite, azurite and pyrite of Waziristan Agency. An investigation of the complexes formed between Cu (II) and Fe (III) in the presence of hydrochloric acid and thiocyanate were carried out and extractability ofCu(II)-SCN complex by two types ofiong chain high moleculer weight amines (HMWA) Alamine 336 and Tribenzylamine were examined. The extractrion of the thiocyanate complex by high molecular weight amines indicate that the species are anionic in nature. The results achieved were.successful and gave better results than the existing methods.